Digital Media For Early Childhood Education During The Covid-19 Pandemic In Cirebon - Suzana Suzana (Annual Conference on Islamic Early Childhood Education (ACIECE), 2022)
The impact of the Covid - 19 pandemic is being felt by all levels of society and all aspects of life, including early childhood education. Changes in learning begin with planning, strategy, media to evaluation. The survey methodology of 175 teachers contains semi-structured questions distributed via Google form which aims to obtain extensive data on the impact of the COVID-19 pandemic on early childhood education units in Cirebon. Data were analyzed descriptively using the framework of social change theory. The findings show that the obstacles faced include the unpreparedness of educators in applying gadgets and the internet as e-learning media, limitations of parents in operating features in gadgets, locations that are difficult to reach by internet access, economic limitations to fulfill study quotas, support and synergy between teachers and parents towards the e-learning process which is still difficult to build